Altruistic acting caused by a touching hand: neural underpinnings of the Midas touch effect. Issue 5 (8th November 2021) - Schaefer, Michael; Kühnel, Anja; Rumpel, Franziska; Gärtner, Matti
Abstract: Giving and receiving touch are some of the most important social stimuli we exchange in daily life. By touching someone, we can communicate various types of information. Previous studies have also demonstrated that interpersonal touch may affect our altruistic behavior. A classic study showed that customers give bigger tips when they are lightly touched by a waitress, which has been called the Midas touch effect. Numerous studies reported similar effects of touch on different kinds of helping or prosocial behaviors. Here, we aim to examine the neural underpinnings of this effect by employing a functional magnetic resonance imaging approach. While lying in the scanner, participants played different rounds of the dictator game, a measure of prosocial behavior. Before each round, participants were touched (or not touched in the control condition) by an experimenter. We found that touching the hand increased the likeliness to behave prosocial (but not the general liking of control stimuli), thereby confirming the Midas touch effect. The effect was predicted by activity in the primary somatosensory cortex, indicating that the somatosensory cortex here plays a causal role in prosocial behavior. We conclude that the tactile modality in social life may be much more important than previously thought.